TEACHER DESIGNED INTERACTIVE WHITEBOARD GAMES IN PRIMARY RUSSIAN LANGUAGE LESSONS (International Conference on Education, Psychology and Humanities, 2026)
The article addresses teacher-designed interactive whiteboard games as an instructional approach for teaching Russian to primary-school pupils aged 7 through 10. 6 canonical IWB manipulations identified by D.Miller, D.Glover and D.Averis and systematised by S.E.Higgins, G.Beauchamp and D.Miller are mapped to the linguistic demands of early Russian-as-foreign-language instruction, including Cyrillic alphabet recognition, lexical retrieval, phonemic discrimination and verb conjugation. Meta-analytic evidence for IWB effectiveness is drawn from Y.Shi, J.Zhang, H.Yang and H.H.Yang, with engagement data from K.Murcia and R.Sheffield. Findings indicate that the pedagogical effect of IWB games depends primarily on teacher design competence rather than on hardware. Recommendations for Uzbek primary classrooms address teacher training and accumulation of game-template libraries.
Keywords: interactive whiteboard, Russian as a foreign language, primary school, teacher-designed games, Cyrillic alphabet, drag and drop, dialogic teaching, multimodal pedagogy, SMART Notebook, ActivInspire, Uzbekistan, classroom technology.